Combination cancer immunotherapy targeting TNFR2 and PD-1/PD-L1 signaling reduces immunosuppressive effects in the microenvironment of pancreatic tumors - Yi Duan; Wen Chen; Jian Xu; Xiaoyu Zhang; Xiaozhen Zhang; Tingbo Liang; Xueli Bai; Mengyi Lao; Hanshen Yang; Muchun Li; Honggang Ying; Lihong He; et al. (Journal for ImmunoTherapy of Cancer)
Backgrounds In advanced pancreatic ductal adenocarcinoma (PDAC), immune therapy, including immune checkpoint inhibitors, has limited efficacy, encouraging the study of combination therapy.Methods Tumor necrosis factor receptor 2 (TNFR2) was analyzed via immunohistochemistry, immunofluorescence, western blotting, and ELISAs. The in vitro mechanism that TNFR2 regulates programmed cell death 1 ligand 1 (PD-L1) was investigated using immunofluorescence, immunohistochemistry, flow cytometry, western blotting, and chromatin immunoprecipitation (ChIP). In vivo efficacy and mechanistic studies, using C57BL/6 mice and nude mice with KPC cell-derived subcutaneous and orthotopic tumors, employed antibodies against TNFR2 and PD-L1. Survival curves were constructed for the orthotopic model and a genetically engineered PDAC model (LSL-KrasG12D/+; LSL-Trp53R172H/+; Pdx1-Cre). Mass cytometry, immunohistochemistry, and flow cytometry analyzed local and systemic alterations in the immunophenotype.Results TNFR2 showed high expression and is a prognostic factor in CD8+ T cell-enriched pancreatic cancer. TNFR2 promotes tumorigenesis and progression of pancreatic cancer via dual effect: suppressing cancer immunogenicity and partially accelerating tumor growth. TNFR2 positivity correlated with PD-L1, and in vitro and in vivo, it could regulate the expression of PDL1 at the transcription level via the p65 NF-κB pathway. Combining anti-TNFR2 and PD-L1 antibodies eradicated tumors, prolonged overall survival in pancreatic cancer, and induced strong antitumor immune memory and secondary prevention by reducing the infiltration of Tregs and tumor-associated macrophages and inducing CD8+ T cell activation in the PDAC microenvironment. Finally, the antitumor immune response derived from combination therapy is mainly dependent on CD8+ T cells, partially dependent on CD4+ T cells, and independent of natural killer cells.Conclusions Anti-TNFR2 and anti-PD-L1 combination therapy eradicated tumors by inhibiting their growth, relieving tumor immunosuppression, and generating robust memory recall.